Prospective analysis of primary open reduction and internal fixation by reconstruction plate for the treatment of midshaftclavicular fractures with greater than 100% displacement in active adult patients - Chowdhury, AKM; Kazi, Begum Dilruba; Rahman, Mizanur; Hossain, Sharmin; Rahman, Molla Mizanur; Amin, Md Ruhul (Journal of Dhaka National Medical College & Hospital, 2017)
Clavicle fracture is one of the most common bony injuries, rarely requires internal fixation. The most frequent indication for open reduction and internal fixation is non-union. Thompson1, based on review of 135 non-unions, found 117 (90%) were middle-third fractures with greater than 100% displacement. He estimated the incidence of this fracture type to be only 3% of all Clavicle fractures and suggested that consideration be made for primary internal fixation in this group. In this study, primary Open reduction and internal fixation by reconstruction plate was done in 26 patients with mid-shaft fracture of the clavicle with greater than 100% displacement. All the patients were followed up for one year to see the consequences of treatment. All the fractures were united. Average duration of fracture union was 16.2±2.2 weeks. Only one patient developed delayed union. There were no symptomatic malunion. All the patients regained full range of movements at the end of follow up. Functional outcomes of the patients were excellent with the mean Disabilities of Arm, Shoulder and Hand score of 6.4±2.4 and the mean Constant score of 90.4 ±4.2 points for the injured side at one year. So we recommended that primary Open reduction and internal fixation by reconstruction plate is a good option of treatment for mid-clavicular shaft fracture with greater than 100% displacement J. Dhaka National Med. Coll. Hos. 2017; 23 (01): 22-25